Economic Cycles: Influence on the Innovation System of Russia - KOSOV, Mikhail Evgenievich (Journal of Advanced Research in Law and Economics, 2019)
Due to the current speed of the changes in all fields and aspects of business activities, the countries that slowly adapt to new realities and pay insufficient attention (preventive attention, in particular) to ideas in the field of science and technology, as well as to mechanisms for bringing them to practical implementation lag behind the advanced countries. The goal of the study is to identify the main problems and limitations of forming an innovation system of Russia. The research methods include synthesis and analysis of statistical data, as well as comparison, formalization, and specification. The problems and limitations of the country's innovation-driven growth have been identified in the study, and methods for solving them have been proposed. There are factors limiting the possibilities of the sustainable economic growth as a result of the exhausted sources of meeting the needs of the society with the current level of development of productive forces and the consumption pattern prevailing today. This situation has largely formed under the influence of internal factors. To solve the problems that have arisen, the economy needs to increase the government spending, to expand credit opportunities, and to use the reserves accumulated earlier by the state. This should help ensure effective demand and enhance business activities.